Differences in Perceptions of Patient Safety Culture between Charge and Noncharge Nurses: Implications for Effectiveness Outcomes Research - Deleise Wilson; Richard W. Redman; AkkeNeel Talsma; Michelle Aebersold (Nursing Research and Practice)
The implementation of evidence-based practice guidelines can be influenced by nurses’ perceptions of the organizational safety culture. Shift-by-shift management of each nursing unit is designated to a subset of staff nurses (charge nurses), whom are often recruited as champions for change. The findings indicate that compared to charge nurses, noncharge nurses were more positive about overall perceptions of safety (𝑃=.05) and teamwork (𝑃<.05). Among charge nurses, significant differences were observed based on the number of years’ experience in charge: perception of teamwork within units [𝐹(3,365)=3.52, 𝑃<.01]; overall perceptions of safety, [𝐹(3,365)=4.20, 𝑃<.05]; safety grade for work area [𝐹(3,360)=2.61, 𝑃<.05]; number of events reported within the last month [𝐹(3,362)=3.49, 𝑃<.05]. These findings provide important insights to organizational contextual factors that may impact effectiveness outcomes research in the future.